Topological types of actions on curves. (September 2023) - Conti, Diego; Ghigi, Alessandro; Pignatelli, Roberto
Abstract: We describe an algorithm that constructs a list of all topological types of holomorphic actions of a finite group on a compact Riemann surface C of genus g ≥ 2 with C / G ≅ P 1 .